Estudo da pirólise da biomassa de dendê como fonte de energia - OLIVEIRA, Brenda Fernanda Honorato de (2019)
The thermochemical pyrolysis process is a form processing of the lignocellulosic matter raw palm (Elaeis guineesis) to obtain higher energy value products, such as Charcoal, bio-oil and gases. In this work was done pyrolysis Empty fruit bunches (EFB) and Oil palm mesocarp fiber (OPMF) at temperature of 400, 500 and 600 ºC, to evaluate the quality of the products obtained. To this it was made the characterization of raw materials for water content analysis, volatile matter, ash, fixed carbon, fiber and calorific value. The solid product was characterized for water content analysis, volatile matter, ash, fixed carbon and calorific value, and the liquid product was characterized by density, viscosity, pH and calorific value. Through the program “Statistica 7.0” was possible analyses that both the BWF as OPMF had higher conversion to solid at a temperature of 400°C, and liquid product at 500 to 600°C. The calorific value of the raw materials was 17, 00 and 19, 00 MJ/kg, to EFB and OPMF respectively. The solid product obtained calorific value between 28, 00 - 29, 00 MJ/kg to BWF and OPMF; this shows the efficiency of pyrolysis for converting liquids and solids. The use of lignocellulosic materials had major advantages for thermochemical processes, because they are good energy sources, It incorporates the use of compounds of vegetable matrices along with the preservation of the environment through the use of biomass for the production of biofuels. The two raw materials presented capacity for the production of liquid and solid fuels.